KETAMIR-2, a new molecular entity and novel ketamine analog - Angel, Itzchak; Perelroizen, Rita; Deffains, Wendy; Adraoui, Florian W.; Pichinuk, Eddy; Aminov, Erez (Frontiers in Pharmacology, 2025)
Ketamir-2 is a new molecular entity, and a novel ketamine analog designed to improve oral bioavailability, and offer a superior safety profile compared to existing ketamine treatments. It was found that Ketamir-2 is a low affinity NMDA receptor antagonist, that selectively binds to the PCP site. Its IC50 on this receptor site is ∼100 µM. Ketamine acts as an NMDA receptor antagonist (0.5–1 µM affinity) and influences opioid receptors, monoaminergic systems (such as serotonin and dopamine). The selectivity of Ketamir-2 was evaluated across a broad range of receptors, transporters, and binding sites, but no activity was detected. Ketamir-2 is a lower affinity and selective PCP-site NMDA antagonist, compared with ketamine. Upon oral administration, Ketamir-2 does not induce hyperlocomotion in mice. Thus, it is different from Ketamine, which induces marked hyperlocomotion, a behavior which is thought to mimic the psychomotor agitation and disorganized behavior seen in schizophrenia, often linked to disruptions in brain neurotransmitter systems. Ketamir-2 was also evaluated via several pharmacological tests in mice to evaluate its anti-depressive and anxiolytic effects. These tests included the Open Field test (OFT), Elevated Plus Maze (EPM), and Forced Swimming Test (FST); all of which are commonly employed behavioral assays used to evaluate the efficacy of anxiety and depression medications. While showing significant effects in these tests at variable doses, ketamine, which was used as a positive control, did not differ from vehicle treatment or showed an opposite response to Ketamir in the majority of the tests studied.